Mechanisms of phenolic biosynthesis induced by ultrasound stress in fresh-cut red cabbages based on energy metabolism analysis - Ningning Ouyang; Chen Hong; Lina Guo; Xinyan Zhang; Wenjuan Qu; Haile Ma (Food Physics)
In our previous studies, ultrasonic washing was proven to induce phenolic biosynthesis in fresh-cut red cabbages; however, the related regulatory mechanisms remain unclear. In response, this study investigates the mechanisms of phenolic biosynthesis in fresh-cut red cabbages under ultrasound stress from the perspective of energy metabolism. The effects of exogenous adenosine triphosphate (ATP) and 2,4-dinitrophenol (DNP) on the phenolic biosynthesis and antioxidant enzymes of fresh-cut red cabbages were also studied. The results show that ultrasound treatment induces the activities of adenosine triphosphatases (ATPase), succinate dehydrogenase (SDH), and cytochrome oxidase (CCO), thus maintaining the high-energy status of fresh-cut red cabbages during storage, primarily characterized by an increase in ATP content and energy charge (EC). The high-energy status is beneficial for providing energy to the biosynthesis of phenolic compounds. In addition, the phenolic content, as well as the activities of phenylalanine ammonia-lyase (PAL), cinnamate-4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX), was increased in the fresh-cut red cabbages after ATP treatment, whereas DNP treatment showed the opposite effect. The results indicate that energy plays an essential role in regulating the antioxidant systems of fresh-cut red cabbages. The energy enhancement induced by ultrasound treatment is a key reason to promote the biosynthesis of non-enzymatic antioxidant–phenolic compounds and enhancing antioxidant enzyme activities. Therefore, the increase in energy levels induced by ultrasonic washing is closely related to the accumulation of phenolic compounds. Positive energy regulation could be a potential mechanism to improve the nutritive value of fruits and vegetables subjected to ultrasonic washing.